Employers' views of the "Healthy Hub Roadshow": a workplace HIV testing intervention in England*. Issue 2 (1st February 2019) - Blake, Holly; Hussain, Basharat; Hand, Jenny; Juma, Amdani; Evans, Catrin
ABSTRACT: We explored employer uptake and perceptions of workplace human immunodeficiency virus (HIV) testing delivered to employees as part of Healthy Hub Roadshow, a multi-component general health check. Intervention included health checks with tailored advice delivered to 776 employees at 20 events hosted by 11 different workplaces (29 approached, 38% employer uptake). Delivery partners were third sector organisations with significant expertise in HIV testing and support. Health checks included optional HIV test (using 4th generation Insti finger prick rapid tests), Body Mass Index (BMI), blood glucose, blood pressure, and cholesterol. Mixed-methods evaluation included post-event online survey and qualitative interviews with participating employers. Declining employers were invited to complete an online feedback survey. Workplace HIV testing was positively received by all participating organisations, although 78% (14/18) of declining organisations did not provide their reasons for non-participation. Factors of importance to employers included the perceived trustworthiness of delivery partners, being able to provide engaging opportunities for employee health, offering HIV testing as part of a wider health check, and having visible top-level managerial support. Concerns about hosting the events were rare and related to having limited budgets for future events, and the potential loss of productivity related to attendance during work time. Employers indicated that they would not actively seek out workplace HIV testing as part of health promotion efforts, but they were highly receptive to its inclusion in workplace health and wellbeing provision by credible external delivery partners. In conclusion, workplaces are an untapped arena for HIV awareness raising and testing in the UK. Employers should be encouraged and supported to offer opt-in HIV testing as part of a wider workplace health and wellbeing provision for employees.